Diabetic kidney disease progression is associated with decreased lower-limb muscle mass and increased visceral fat area in T2DM patients - Lin, Xiaopu; Chen, Zhenguo; Huang, Haishan; Zhong, Jingyi; Xu, Lingling (Frontiers in Endocrinology, 2022)
Aim: This study aimed to explore the relationship between lower-limb muscle mass/visceral fat area and diabetic kidney disease (DKD) progression in patients with type 2 diabetes mellitus (T2DM). Methods: A total of 879 participants with T2DM were divided into 4 groups according to the prognosis of CKD classification from Kidney Disease: Improving Global Outcomes (KDIGO). Rectus femoris cross-sectional area (RFCSA) was measured through ultrasound, and visceral fat area (VFA) was evaluated with bioelectric impedance analysis (BIA). Results: T2DM patients with high to very high prognostic risk of DKD showed a reduced RFCSA (male P < 0.001; female P < 0.05), and an enlarged VFA (male P < 0.05; female P < 0.05). The prognostic risk of DKD was negatively correlated with RFCSA (P < 0.05), but positively correlated with VFA (P < 0.05). Receiver-operating characteristic analysis revealed that the cutoff points of T2DM duration combined with RFCSA and VFA were as follows: (male: 7 years, 6.60 cm2, and 111 cm2; AUC = 0.82; 95% CI: 0.78–0.88; sensitivity, 78.0%; specificity, 68.6%, P < 0.001) (female: 9 years, 5.05 cm2, and 91 cm2; AUC = 0.73; 95% CI: 0.66–0.81; sensitivity, 73.9%; specificity, 63.3%, P < 0.001). Conclusion: A significant association was demonstrated between reduced RFCSA/increased VFA and high- to very high-prognostic risk of DKD. T2DM duration, RFCSA, and VFA may be valuable markers of DKD progression in patients with T2DM. Keywords: Diabetic kidney disease; Sarcopenia; Abdominal obesity; Visceral fat area; Type 2 diabetes mellitus Clinical Trial Registry: Chinese Clinical Trials Registry ChiCTR2100042214.